Rebel angels : space and sovereignty in Anglo-Saxon England - Fitzgerald, Jill (Manchester medieval literature and culture., 2019)
Over six hundred years before John Milton's Paradise Lost, Anglo-Saxon authors told their own version of the fall of the angels. This book brings together various cultural moments, literary genres and relevant comparanda to recover that version, from the legal and social world to the world of popular spiritual ritual and belief. The story of the fall of the angels in Anglo-Saxon England is the story of a successfully transmitted exegetical teaching turned rich literary tradition. It can be traced through a range of genres - sermons, saints' lives, royal charters, riddles, devotional and biblical poetry - each one offering a distinct window into the ancient myth's place within the Anglo-Saxon literary and cultural imagination.